Bio-inspired leading-edge tubercles to improve fatigue life in horizontal axis wind turbine blades - Ng,BF; New,TH; Palacios,R (2017)
© 2017, American Institute of Aeronautics and Astronautics Inc, AIAA. All rights reserved. Bio-inspired leading-edge tubercles are known to improve aerodynamic performances during stall but there could be additional advantages in other operating regimes and their effect on aeroelastic loadings is also less understood. In this study, the effect of leading-edge tubercles on fatigue loadings on wind turbine blades is investigated using an aeroelastic model that couples a composite beam to the unsteady vortex-lattice method. To accommodate the leading-edge tubercles, spanwise structural properties and aerodynamic geometries are varied, which resulted in a reduction in both torsional frequencies and aerodynamic lift despite keeping the same planform area. The reductions in structural frequencies and aerodynamics have counteracting effects on fatigue responses, with the former increasing and the latter reducing loads. On a turbine blade with tubercles (amplitude of 0.2c and wavelength of 0.5c) occupying 20% to 95% span of the leading-edge, flapwise root-bending moment was found to be 6% lower than the unmodified configuration, which can be further enhanced with a trough termination at the blade tip. Torsional moment was 17% lower due to the reduction in leading-edge suction along tubercle crests, which are further away from the elastic axis. In terms of tubercle positioning, having tubercles close to the blade tip enables performance enhancement during episodes of stall from large tip deflections and has significant contributions to root-bending moment due to a larger moment arm and higher relative flow speed. On the other hand, positioning tubercles close to the blade root may also be favoured as this region is prone to stall from low speeds, yet having little effect on fatigue responses.